The BLISS Housing Program blissful or blistering? - Domingo, Ma. Oliva Z. (Philippine Journal of Public Administration, 2001)
The Bagong Lipunan Sites and Services Program more popularly known as the BLISS Housing Program was instituted as a means to address the growing housing requirements of the country. More than just providing shelter, the program intended to develop productive, self-reliant communities in an atmosphere that would ensure the physical, intellectual and spiritual well-being of man. This article outlines the BLISS concept within the milieu of the government's housing program, including its most salient features. It eventually narrows down to one major component - the Urban BLISS level. The case of the UP BLISS San Vicente project is illustrated here to give clearer insights on the issues, concepts and strategies utilized in the course of the project's implementation.